Problematic issues of comparability as a qualitative characteristic of useful information in financial statements - S.L.; L.P. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
As a result of globalization and the growth of international trade, the boundaries of business have expanded. The creation of uniform, globally applicable accounting standards should have enabled the comparability of financial reporting information. Users of financial statements need comparable and transparent information. It is believed that comparability as a qualitative characteristic is quite clear and seamless, which confirms our survey of specialists in the field of accounting. Choosing the most important of the two qualitative characteristics, the respondents preferred other qualitative characteristics, comparability is not defined as a characteristic of qualitative reporting information. The article considers the problematic issues of comparability. It is determined that in terminology there is ambiguity in the interpretation of the term «comparability», defined by IFRS. Comparison is defined as the process by which financial statement items are compared. Comparability is defined as a qualitative characteristic of the article. In the context of financial reporting, it is proposed to develop a strict, methodological approach to comparability, to avoid ambiguity in interpretations.